Two mode Mindlin-Herrmann rod solution based on modified couple stress theory - Guven, Ugur (WILEY-V C H VERLAG GMBH, 2014)
In this work, the classical two mode Mindlin-Herrmann rod model is extended by using the modified couple stress theory having the single internal length scale parameter to investigate the propagation of the longitudinal stress waves along a nanorod. This analysis also contains the single mode Rayleigh-Bishop rod solution based on the modified couple stress theory. Comparative results for the classical Mindlin-Herrmann and the single mode Rayleigh-Bishop rod models based on the modified couple stress theory are presented and discussed. The present analysis shows that Mindlin-Herrmann rod model is influenced significantly by the internal length scale parameter. (C) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: Longitudinal wave propagation; modified couple stress theory; Mindlin-Herrmann rod model; two mode solution; Rayleigh-Bishop rod model; WAVES; Mathematics; Mechanics